A Comparative Study Of Medoghna Rasayana Vati & Shilajitwadi Vati In The Management Of Madhumeha W.S.R. To Diabetes Mellitus. - Mohan, G Vinay; Rao, P Shrinivas; patilbuva, Khaire Ajit (International Research Journal of Ayurveda & Yoga, 2020)
Besides the miraculous achievement of modern medical science, humanity is passing through a horror of disease and drug phobia, particularly in developing countries like India, where poverty and illiteracy account for the man’s ignorance towards the principles of health care. In modern medical science symptomatology of Madhumeha is equivalent to the features of Diabetes mellitus. Among the several health problems Diabetes mellitus is a giant disease considered as one of the arch enemies of the mankind. Diabetes and its complications pose a major threat to future public health resources throughout the world. The Ayurvedic management of Diabetes aims not only to achieve a strict glycemic control but also to treat the root cause of the disease. For its various modalities of treatment are developed which depends upon the underline pathology. Madhumeha has been classified under the Vatika type of Prameha. The Vata may be provoked either directly by its etiological factors, Avarana by Kapha and Pitta to its path or by continuous depletion of Dhatus. Vagbhata has classified the Madhumeha into two categories viz. Dhatukshayajanya Madhumeha and Avaranajanya Madhumeha. The factors which provoke the Vata directly causes Apatarpanajanya Madhumeha while the factors which provoke Kapha and Pitta causes Santarpanajanya Madhumeha. The Apatarpanajanya Madhumeha patients are usually Asthene and are equivalent to Type I Diabetes mellitus, while the Santarpanajanya Madhumeha patients are Obese equivalent to Type II Diabetes mellitus. In Avaranajanya Madhumeha, Kapha is the predominant Dosha while the important Dushyas are Meda and Kleda. Type 2 Diabetes mellitus is mainly associated with Avaranajanya Samprapti. In Madhumeha, the main Avaraka are Kapha, Pitta, Rasa, Mamsa and Meda, and out of these Meda is predominant. Principle of management of Avarana is Sramsana, Rasayana treatment and the use of Medoghna Dravyas. Hence the formulations of Medoghna Rasayana Vati & Shilajitwadi Vati is indicated, especially in treating the Madhumeha.